2012
DOI: 10.1155/2012/891841
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 2,4-Thiazolidinedione on Limousin Cattle Growth and on Muscle and Adipose Tissue Metabolism

Abstract: The main adipogenic transcription factor PPARγ possesses high affinity to 2,4-TZD, a member of the Thiazolidinedione family of insulin-sensitizing compounds used as adipogenic agents. We evaluated 2,4-TZD's effect on bovine growth and PPAR tissue expression. Seventeen Limousin bulls (18 month-old; 350 kg body weight (BW)) were assigned into 2 treatments: control and 2,4-TZD (8 mg/70 kg BW) and were fed until bulls reached 500 kg BW. They were weighed and their blood was sampled. DNA, RNA, and protein were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…More adipocytes and larger cell sizes have been observed in mice supplemented with PGZ [13,14,18]. According to previous reports, PGZ has the potential to promote fat deposition in animal muscle [19,20]. Consistent with these findings, our previous studies confirmed that dietary supplementation with 15 mg/kg PGZ can increase the IMF in the longissimus thoracis muscle of pigs [21,22].…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…More adipocytes and larger cell sizes have been observed in mice supplemented with PGZ [13,14,18]. According to previous reports, PGZ has the potential to promote fat deposition in animal muscle [19,20]. Consistent with these findings, our previous studies confirmed that dietary supplementation with 15 mg/kg PGZ can increase the IMF in the longissimus thoracis muscle of pigs [21,22].…”
Section: Introductionsupporting
confidence: 88%
“…From the present and some previous studies [13][14][15][16][17][18][19][20][21][22], we can conclude that dietary PGZ can increase muscle fat deposition and improve the meat quality of food animals. It has potential as a new functional feed additive.…”
Section: Discussionsupporting
confidence: 63%
“…7 In studies of ruminants, intramuscular adipose deposition has already been demonstrated to be increased by dietary supplementation with PGZ. 8 In our early exploration, PGZ also showed a positive effect on IMF and the marbling score of finishing pigs. 9,10 However, it is still unclear whether PGZ supplementation would improve poultry meat quality and increase IMF.…”
Section: Introductionmentioning
confidence: 77%
“…Pioglitazone hydrochloride (PGZ), a high‐affinity ligand of PPAR γ , therefore interested us . In studies of ruminants, intramuscular adipose deposition has already been demonstrated to be increased by dietary supplementation with PGZ . In our early exploration, PGZ also showed a positive effect on IMF and the marbling score of finishing pigs .…”
Section: Introductionmentioning
confidence: 99%
“…Among the few available studies, it was observed that liver of dairy cows expresses a similar amount of PPARA and PPARD but does not express PPARG [44]. In a recent study where the expression of the three PPAR isotypes was evaluated in liver and muscle of beef bulls, the greatest expression was observed for PPARA , followed by PPARG , with the lowest expression for PPARD in liver, while, the largest expression in muscle was observed for PPARG [71]. This relative distribution among tissues is somewhat comparable to our data (Figure 1(b)).…”
Section: Ppar Isotype Expression In Ruminant Tissuesmentioning
confidence: 99%